2017
DOI: 10.1097/md.0000000000006035
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of hepatic dysfunction in patients with Graves’ hyperthyroidism and the efficacy of 131iodine treatment

Abstract: Hepatic dysfunction is often observed in patients with Graves’ hyperthyroidism. The aims of this study were to investigate the risk factors for hepatic dysfunction and to analyze the efficacy of 131I (radioactive iodine-131) treatment. In total, 2385 patients with Graves’ hyperthyroidism (478 males, 1907 females; age 42.8 ± 13.5 years) were involved in our study. Of these, 1552 cases with hepatic dysfunction received 131I treatment. All clinical data were retrospectively reviewed to explore the risk factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…For patients with thyrotoxicosis-induced cholestasis, rapid restoration of euthyroidism is important for the recovery of liver function. 9 Previous studies have shown that control of hyperthyroidism is important for recovery of cholestasis, induced by MMI or hyperthyroidism. 9,28 However, the choice of treatment methods for hyperthyroidism is complicated in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with thyrotoxicosis-induced cholestasis, rapid restoration of euthyroidism is important for the recovery of liver function. 9 Previous studies have shown that control of hyperthyroidism is important for recovery of cholestasis, induced by MMI or hyperthyroidism. 9,28 However, the choice of treatment methods for hyperthyroidism is complicated in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies discuss the connection between thyroid and liver disease, and 65% of patients with Grave’s disease show some degree of hepatic dysfunction 11. Certain risk factors appear to be correlated with increased risk of developing hepatobiliary disease: older age, longer duration of hyperthyroidism and higher level of TRAb 11 12…”
Section: Discussionmentioning
confidence: 99%
“…The disorders in any of these organs in uence each other causing clinical and laboratory abnormalities. [6] The possible associations could be: liver damage due to excessive thyroid hormones ,autoimmune reactions, changes in thyroid hormone metabolism that is secondary to liver disease, drug-induced liver or thyroid damage due to therapy used for liver or thyroid disease. [4] There are several factors that contributes for development of liver dysfunction in such patients.…”
Section: Page 3/16mentioning
confidence: 99%